MATHEMATICS TEACHERS BELIEFS AND MATHEMATICAL MINDSET TOWARD DIFFERENTIATED INSTRUCTION: AN EXPLORATORY STUDY IN MADRASAH ALIYAH - Abdul Aziz Saefudin; Mahilda Dea Komalasari; Dian Putri Pramitasari (Journal of Authentic Research on Mathematics Education (JARME), 2026)
This small-scale exploratory study examined Madrasah Aliyah mathematics teachers beliefs about differentiated instruction, implementation self-efficacy, mathematical mindset, reported practices, and perceived benefits and barriers. Thirteen mathematics teachers in the Special Region of Yogyakarta completed an online questionnaire containing closed-ended items and one open-ended question. Quantitative data were analysed descriptively, while open-ended responses were examined through content analysis. The findings showed that teachers strongly valued differentiated mathematics instruction (M = 3.31), although implementation self-efficacy was descriptively lower (M = 3.08). Most teachers reported prior experience with differentiation, with process differentiation used more frequently than content and product differentiation. Eleven teachers showed a high-valuehigh-self-efficacy profile, whereas two showed high value with lower self-efficacy. Teachers overall mathematical mindset was classified as growth-fixed (GF), while the effort and persistence item reached growth-growth (GG). The main perceived benefit was accommodating learner diversity, whereas the principal barriers involved time, workload, classroom management, and limited experience. These findings highlight the need for practical and collaborative professional development that helps teachers translate positive beliefs into sustainable differentiated mathematics practices.